The effect of fiber milling on mechanical properties of polypropylene reinforced oil palm mesocarp fiber biocomposite - Ahamad Nordin, Noor Ida Amalina; Ariffin, Hidayah; Hassan, Mohd Ali; Andou, Yoshito; Shirai, Yoshihito; Nishida, Haruo (Faculty of Engineering, Universiti Putra Malaysia, 2012)
Oil palm mesocarp fiber (OPMF) is biomass residue abundantly available at palm oil mill. Being a lignocellulose, it can be used as reinforce material in biocomposite. In this study, the effect of OPMF milling on the mechanical properties of polypropylene (PP)/OPMF biocomposite was studied. Two types of mills were used, i.e. Wiley mill (WM) and disc mill (DM). Ground OPMF from each milling process was examined for its surface morphology, particle size distribution and aspect ratio by microscopic analyses. Ground OPMF was later sieved and fiber with particle size less than 150 μm was separated and mixed with PP using Thermo Haake mixer at 20 and 50 % (w/w) of fiber loading. Results showed that PP/DM-OPMF biocomposite had higher tensile strength compared to PP/WM-OPMF, with almost two-fold. From the SEM and light microscopic analysis, it can be observed that DM-OPMF had smaller diameter of fiber with almost uniform size of particles. Small diameter and uniform size of fiber may improve stress transfer between the fiber and polymer matrix, improve surface contact between polymer matrix and fiber and cause the well-dispersion of filler throughout the polymer. This explains the better tensile strength of PP/DM-OPMF compared to PP/WM-OPMF biocomposite. Overall, it can be concluded that disc milling could serve as a simple and effective grinding method which is able to improve the mechanical properties of biocomposite.